Anxiety, Stress, and Fear Response in Mice With Reduced Endocannabinoid Levels - Jenniches, Imke; Ternes, Svenja; Albayram, Onder; Otte, David M.; Bach, Karsten; Bindila, Laura; Michel, Kerstin; Lutz, Beat; Bilkei-Gorzo, Andras; Zimmer, Andreas (Biological psychiatry (1969), 2016)
Disruption of the endocannabinoid system through pharmacological or genetic invalidation of cannabinoid CB1 receptors has been linked to depression in humans and depression-like behaviors in mice. The two main endogenous cannabinoids, anandamide and 2-arachidonoyl glycerol (2-AG), are produced on demand from phospholipids. The pathways and enzymes involved in endocannabinoid biosynthesis thus play a major role in regulating the activity of this system. This study investigates the role of the main 2-AG producing enzyme diacylglycerol lipase α (DAGL-α). We generated and used knockout mice lacking DAGL-α (Dagla−/−) to assess the behavioral consequences of reduced endocannabinoid levels in the brain. We performed different behavior tests to determine anxiety- and depression-related behavioral changes in Dagla−/− mice. We also analyzed expression of genes related to the endocannabinoid system via real-time polymerase chain reaction and used the mitotic marker 5-bromo-2′-deoxyuridine to analyze adult neurogenesis. Dagla−/− animals show an 80% reduction of brain 2-AG levels but also a reduction in cortical and amygdalar anandamide. The behavioral changes induced by Dagla deletion include a reduced exploration of the central area of the open field, a maternal neglect behavior, a fear extinction deficit, increased behavioral despair, increased anxiety-related behaviors in the light/dark box, and reduced hippocampal neurogenesis. Some of these behavioral changes resemble those observed in animals lacking the CB1 receptor. Our findings demonstrate that the deletion of Dagla adversely affects the emotional state of animals and results in enhanced anxiety, stress, and fear responses.